SCABIES: POLYMORPHIC PRURITIC PAPULAR ERUPTION IN A PATIENT WITH PULMONARY TUBERCULOSIS - AID OF DERMOSCOPY - Alves, Andreia Oliveira; Filho, Fred Bernardes; Martins, Gustavo; Nogueira, Letycia Lopes Chagas; Lanza, Thais de Abreu; Nery, José Augusto da Costa (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
We report a case of a 62-years-old male patient with pulmonary tuberculosis newly diagnosed who presented a polymorphic eruption due to an infestation by Sarcoptes scabiei. The authors demonstrate dermoscopic findings of human scabies and emphasize the importance of the use of dermoscopy as a valuable tool in non-traditional indications of its use.